2022
DOI: 10.1136/lupus-2022-000756
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular adipose tissue in patients with systemic lupus erythematosus

Abstract: ObjectivePatients with SLE frequently have debilitating fatigue and reduced physical activity. Intermuscular adipose tissue (IMAT) accumulation is associated with reduced physical exercise capacity. We hypothesised that IMAT is increased in patients with SLE and associated with increased fatigue, reduced physical activity and increased inflammation.MethodsIn a cross-sectional study, 23 patients with SLE and 28 control participants were evaluated. IMAT was measured in the calf muscles using sequentialT1-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For example, patients with SLE werereported to exhibit greater extent of visceral adipose tissue deposition than controls (Li et al 2019 ), which—together with the greater perivascular adipose depots reported in rheumatic diseases including SLE (Shi et al 2022 )—predisposes them for cardiovascular complications. As reported for other rheumatic diseases such as RA (Baker et al 2018 ), intermuscular adipose tissue deposition is also reported in SLE (Gamboa et al 2022 ) and contributes significantly to poorer long-term strength of patients. In addition, given the large number of adipokines secreted within adipose tissue, it is not unexpected that obesity has been identified as a major contributor to sustained pro-inflammatory dysregulation and disease progression in rheumatic disease (Versini et al 2014 ), as well as specifically in renal inflammation and fibrosis (Declèves and Sharma 2015 ).…”
Section: Cellular Pathology In Lupus Nephritis: the Bmp-7 Linkmentioning
confidence: 59%
“…For example, patients with SLE werereported to exhibit greater extent of visceral adipose tissue deposition than controls (Li et al 2019 ), which—together with the greater perivascular adipose depots reported in rheumatic diseases including SLE (Shi et al 2022 )—predisposes them for cardiovascular complications. As reported for other rheumatic diseases such as RA (Baker et al 2018 ), intermuscular adipose tissue deposition is also reported in SLE (Gamboa et al 2022 ) and contributes significantly to poorer long-term strength of patients. In addition, given the large number of adipokines secreted within adipose tissue, it is not unexpected that obesity has been identified as a major contributor to sustained pro-inflammatory dysregulation and disease progression in rheumatic disease (Versini et al 2014 ), as well as specifically in renal inflammation and fibrosis (Declèves and Sharma 2015 ).…”
Section: Cellular Pathology In Lupus Nephritis: the Bmp-7 Linkmentioning
confidence: 59%
“…Serum lipoproteins were measured by nuclear magnetic resonance and analyzed by the Bruker IVDr Lipoprotein Subclass Analysis, as previously described. 21 HDL purification. HDL was separated from 8 mL plasma by density-gradient ultracentrifugation for sequential isolation of lipoprotein-containing subfractions using potassium bromide: very low-density lipoprotein (1.006-1.018 g/mL), LDL (1.019-1.063 g/mL), and HDL (1.064-1.021 g/mL), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…High‐sensitivity CRP was measured in the Vanderbilt University Medical Center Hospital Laboratory. Serum lipoproteins were measured by nuclear magnetic resonance and analyzed by the Bruker IVDr Lipoprotein Subclass Analysis, as previously described 21 …”
Section: Methodsmentioning
confidence: 99%
“…IMAT was segmented using an automated unsupervised learning algorithm, specifically k‐means clustering, to separate areas of IMAT from the muscle segmentation in the fat‐weighted Dixon MRI image. The IMAT segmentation was then used to calculate the percentage of IMAT area relative to total muscle area (%) at the level of the mid‐calf (Gamboa et al., 2022 ; Sahinoz et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%